Creating Normalcy: Foster Care for Children and Youth with Disabilities and Medical Fragility in Germany - Föltz, Friedegard (International Journal of Child, Youth and Family Studies)

(untitled) (University of Victoria, 2020)
In the area of foster care concerning children and youth with special needs due to disability or medical fragility, there is a paucity of knowledge and research. In Germany, these groups in foster care who have high special needs are an invisible and neglected population at risk. These children and youth are mostly cared for in residential homes; however, some are living in foster families and benefit from a familial setting. The purpose of the study was to understand how foster parents manage their lives with a child or youth who has special needs, and how they meet the challenges that arise. The qualitative research design used the method of narrative inquiry through in-depth interviews, which were conducted in the German state of Saxony-Anhalt with 19 foster parents from 15 families. Within the framework of grounded theory, the author developed a theoretical structure of the strategies foster parents use for coping. Results showed that foster parents dealt with this new and often unpredictable situation by applying one of three patterns of strategies — action-, resource-, or reflection-oriented — based on their personal experiences and worldview. Understanding these behavioral patterns gives administrative and supportive entities like child welfare systems and agencies a unique and tailored approach to recruit, retain, train, and counsel foster families adequately, and to strengthen their well-being and their ability to perform well for themselves and their children and youth.